Answer:
-3x is the answer I'm pretty sure I think
Answer:
f(- 6) = 70
Step-by-step explanation:
To evaluate f(- 6) , substitute x = - 6 into f(x)
f(- 6) = 2(- 6)² - 2 = 2(36) - 2 = 72 - 2 = 70
Answer:
is this weird but in all my years of school I've never learn something like this
Answer:
D) -0.87
Step-by-step explanation:
I took this test don't quote me on the answer but this is what my peers put.
Point-slope form of equation is: ![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Step-by-step explanation:
Given points are:
(2,-8) and (1,7)
First of all we have to calculate the slope of the line
so,
![m=\frac{y_2-y_1}{x_2-x_1}\\= \frac{7-(-8)}{1-2}\\=\frac{7+8}{-1}\\=\frac{15}{-1}\\= -15](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%5C%5C%3D%20%5Cfrac%7B7-%28-8%29%7D%7B1-2%7D%5C%5C%3D%5Cfrac%7B7%2B8%7D%7B-1%7D%5C%5C%3D%5Cfrac%7B15%7D%7B-1%7D%5C%5C%3D%20-15)
Point-slope form is given by:
![y-y_1 = m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%20%3D%20m%28x-x_1%29)
Putting the value of slope
![y-y_1 = -15(x-x_1)](https://tex.z-dn.net/?f=y-y_1%20%3D%20-15%28x-x_1%29)
We can put any one of two given points in the equation to find the final form of point-slope form
So
Putting (1,7) in the equation
![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Hence, point-slope form of equation is: ![y - 7 = -15(x-1)](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29)
Reducing and simplifying
![y - 7 = -15(x-1)\\y-7 = -15x+15\\y-7+7 =-15x+15-7\\y = -15x+8\\15x+y = 8](https://tex.z-dn.net/?f=y%20-%207%20%3D%20-15%28x-1%29%5C%5Cy-7%20%3D%20-15x%2B15%5C%5Cy-7%2B7%20%3D-15x%2B15-7%5C%5Cy%20%3D%20-15x%2B8%5C%5C15x%2By%20%3D%208)
Keywords: Point-slope form, equation of line
Learn more about equation of line at:
#LearnwithBrainly